2010
DOI: 10.1038/ijo.2010.61
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, adiposity rebound and early feeding in a longitudinal cohort (Raine Study)

Abstract: Objective: This study examined the influence of type and duration of infant feeding on adiposity rebound and the tracking of body mass index (BMI) from birth to 14 years of age. Methods: A sample of 1330 individuals over eight follows-ups was drawn from the Western Australian Pregnancy Cohort (Raine) Study. Trajectories of BMI from birth to adolescence using linear mixed model analysis investigated the influence of age at which breastfeeding was stopped and the age at which other milk was introduced (binomial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
16

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 24 publications
3
77
0
16
Order By: Relevance
“…Comparable with the present study, Ong et al (34) found that dietary energy intake at 4 months was associated with larger body weight SDS among formula-or mixed-fed children, but not with breast-fed children. Another study concerning BMI and early feeding by Chivers et al (42) also stresses the importance of exclusive breast-feeding for at least 4 months. Comparable with the present study, Bulk-Bunschoten et al (28) found that mothers from Turkish and Moroccan origin breast-fed more and with a longer duration compared with Dutch mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable with the present study, Ong et al (34) found that dietary energy intake at 4 months was associated with larger body weight SDS among formula-or mixed-fed children, but not with breast-fed children. Another study concerning BMI and early feeding by Chivers et al (42) also stresses the importance of exclusive breast-feeding for at least 4 months. Comparable with the present study, Bulk-Bunschoten et al (28) found that mothers from Turkish and Moroccan origin breast-fed more and with a longer duration compared with Dutch mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports including ours showed that the onset of adiposity rebound (AR), the point at which the BMI starts to increase after its nadir, occurred earlier in 21-OHD patients than in normal children [5,11]. Premature AR has been identified as one of the possible contributory factors in adult obesity and metabolic syndrome [9,7,[12][13][14][15][16]. We hypothesized that fetal and early infantile factors, including birth size and glucocorticoid therapy, could affect the timing of AR.…”
Section: -Hydroxylase Deficiency (21-ohd) Ismentioning
confidence: 99%
“…Premature AR has been identified as one of the possible contributory factors in adult obesity and metabolic syndrome [9,7,[12][13][14][15][16]. We hypothesized that fetal and early infantile factors, including birth size and glucocorticoid therapy, could affect the timing of AR.…”
mentioning
confidence: 99%
“…de 2010, en el que establecen que una lactancia materna inferior a 4 meses de duración predispone a mayor IMC a los 14 años. Todo esto confirma la importancia de la lactancia materna exclusiva durante más de 4 meses como un factor protector contra el desarrollo de la obesidad del niño y el adolescente (20). Lo que también se ve apoyado por el estudio de De Kroon y cols.…”
Section: Discussionunclassified